Full or intensity‐reduced high‐dose melphalan and single or double autologous stem cell transplant with or without bortezomib consolidation in patients with newly diagnosed multiple myeloma. (28th August 2021) - Straka, Christian; Salwender, Hans; Knop, Stefan; Vogel, Martin; Müller, Jürgen; Metzner, Bernd; Langer, Christian; Sayer, Herbert; Jung, Wolfram; Dürk, Heinz A.; Bassermann, Florian; Gramatzki, Martin; et al.
Abstract: Objective: A post hoc subgroup analysis of two phase III trials (NCT00416273, NCT00416208) was carried out to investigate the influence of 100/140 and 200 mg/m² melphalan as well as single/double autologous stem cell transplantation (ASCT) on progression‐free survival (PFS). Additionally, the effect of bortezomib consolidation on PFS was analyzed. Methods: Following induction therapy and high‐dose melphalan with subsequent ASCT, patients with newly diagnosed multiple myeloma (NDMM) were randomized 1:1 to either four 35‐day cycles of bortezomib consolidation (1.6 mg/m² IV on days 1, 8, 15, 22) or observation. Results: Of the 340 patients included in this analysis, 13.5% received 1 × MEL100/140, 22.9% 2 × MEL100/140, 31.2% 1 × MEL200, and 32.4% 2 × MEL200. With higher cumulative melphalan dose, PFS improved ( P = .0085). PFS curves of patients treated with 2 × MEL100/140 and 1 × MEL200 were very similar. The superior dose effect of MEL200 over MEL100/140 was non‐existent in the bortezomib consolidation arm but pronounced in the observation arm ( P = .0015). Similarly, double ASCT was only beneficial in patients without bortezomib consolidation ( P = .0569). Conclusions: Full dose melphalan and double transplantation seem advantageous only as long as patients are not receiving bortezomib consolidation afterwards.